Floating debris in the Portuguese continental offshore waters - Sá, Sara Maria Fardilha Alves de (2014)
Floating marine debris are present throughout the oceans and may have negative impacts on marine fauna, such as entanglement, ingestion and transport of exotic species. The present work aims at obtaining estimates of abundance and density of floating marine debris and vessels, as well as their spatial distributions along the entire study area. It also aims at identifying areas of spatial overlap between marine debris, cetaceans and vessels. The sighting surveys were performed during the summer of 2011, aboard the sailing vessel Santa Maria Manuela. This campaign was part of the project LIFE+ MARPRO - Conservation of marine protected species in Mainland Portugal, and the study area ranged between the 50 and the 220 nautical miles west of Portugal mainland, covering an area of about 252833 Km2. The survey was conducted along line transects, following a methodology that allowed to using conventional distance sampling methods to estimate the abundance and density of floating marine debris and vessels. Mean density (objects per km2) of debris in the study area overall was 2.96 objects per km2 and the total abundance was 747720 floating pieces. Floating plastic was the most common type of debris. In respect of vessels, mean density was 0.0013434 vessels per km2 and the estimated total abundance was 340 vessels.